Publications Received (Academy of Management Review, 1996)
The article presents a bibliography of books relating to the field of management, including “Basic Guide to Industrial Hygiene,” by Jeffrey W. Vincoli, “Business Process Benchmarking: Finding and Implementing Best Practices,” by Robert Camp, and “Causes of Death in the Workplace,” by J. Paul Leigh.